Efficacy of a Topical Product Containing Purified Omental Lipids and Three Anti-Itching Compounds in the Treatment of Chronic Pruritus/Prurigo Nodularis in Elderly Subjects: A Prospective, Assessor-Blinded, 4-Week Trial with Transepidermal Water Loss and Optical Coherence Tomography Assessments - Ardigò M; Franceschini C; Campione E; Cosio T; Lanna C; Bianchi L; Milani M (Dove Medical Press, 2020)
Marco Ardigò,1 Chiara Franceschini,1 Elena Campione,2 Terenzio Cosio,2 Caterina Lanna,2 Luca Bianchi,2 Massimo Milani3 1Clinical Dermatology, San Gallicano Dermatological Institute, Rome, Italy; 2Dermatology Institute, Università Tor Vergata, Rome, Italy; 3Medical Department, Cantabria Labs Difa Cooper, Caronno Pertusella, VA, ItalyCorrespondence: Massimo MilaniMedical Department, Cantabria Labs Difa Cooper, Caronno Pertusella, ItalyEmail massimo.milani@difacooper.comPurpose: To investigate the efficacy of a cream containing purified omental lipids 10% and three anti-itching substances (polidocanol/stimutex/palmitoylethanolamine) in elderly subjects with chronic pruritus/prurigo nodularis (CP/CPN).Patients and Methods: Thirty-five subjects (6 men; mean age 67± 4 years) with CP/CPN were enrolled in a prospective, assessor-blinded, 4-week study. The cream was applied twice daily in the most affected body area. The primary endpoints were the evolution of the 10-cm visual analogue itch severity scale (VAS) and the 4-point verbal itching rating scale (VRS) (from 0 to 3). Secondary endpoints were the evolution of optical coherence tomography (OTC) of four skin parameters (acanthosis/hyperkeratosis/scale/dermal vascular pattern), assessed in a target lesioned area, and the transepidermal water loss (TEWL). Study endpoints were evaluated at baseline and after 2 and 4 weeks by an investigator unaware of the type of treatment.Results: All the enrolled subjects concluded the trial. At baseline, the mean±SD scores for VAS and VRS were 4.9± 2.2 and 1.7± 0.7, respectively. The treatment was associated with a significant reduction (p=0.0001) of VAS score of 60% at week 2 and of 86% at week 4. VRS score was significantly reduced by 49% after 2 weeks and by 81% after 4 weeks, in comparison with baseline. TEWL (expressed as g/m2/h) mean values were 18± 5.4 at baseline and 12.7± 4.4 at week 2 and 9.8± 4.7 at week 4 (P=0.0001 vs baseline). All the OCT parameters evaluated improved during active treatment; acanthosis grade was 0.22 mm at baseline, 0.19 mm at week 2 and 0.17 mm at week 4 (p=0.0005), representing a 23% reduction in comparison with baseline. The product was very well tolerated.Conclusion: This purified omental lipid with three anti-itching components cream reduces significantly itch intensity in subjects with chronic pruritus/prurigo nodularis, improving the skin barrier function and skin structure.Trial Number: ISRCTN869561669.Keywords: chronic pruritus, prurigo nodularis, purified omental lipids, itch, antipruritic